(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
field experiment was conducted during the 2023 dry season at the College of Agriculture, Mokwa, Niger State, Nigeria, to evaluate the effects of poultry and brown bat manures on the growth and marketable yield of two amaranth (Amaranthus) varieties. The experimental site lies within the Southern Guinea Savannah agroecological zone at latitude 09°18′N and longitude 05°04′E. The study employed a factorial arrangement in a Randomized Complete Block Design (RCBD) with three replicates. Treatments included two amaranth varieties—Amaranthus cruentus and A. caudatus—and four application rates (0, 2, 4, and 6 t ha⁻¹) of each manure type. Data were collected on growth parameters and marketable yield and analyzed using the Least Significant Difference (LSD) test at a 5% probability level. Results indicated that A. cruentus produced significantly higher marketable yields (2659.6 kg ha⁻¹) compared to A. caudatus (2252.2 kg ha⁻¹). Among the manure treatments, brown bat manure applied at 4 t ha⁻¹ yielded the highest output (3561.7 kg ha⁻¹), while the control treatment (no manure) recorded the lowest (693.0 kg ha⁻¹). The interaction between manure type and variety also influenced yield outcomes. Based on these findings, it is recommended that farmers in Mokwa and similar agroecological zones adopt A. cruentus variety and apply brown bat manure at 4 t ha⁻¹ to optimize amaranth productivity and market returns.